Kebijakan Daftar Negatif Investasi di Indonesia: Tinjauan Mengenai Perdagangan Bebas dan Konservasi Spesies Ikan yang Terancam Punah - Simbolon, Putu George Matthew (CV. Social Politic Genius (SIGn), 2023)
This study examines and analyzes the problems arising from the interaction between Indonesian investment measures and compliance with the international trade regime. This study uses a normative legal research method. The collected legal material is then qualitatively analyzed to describe the problem and answer the study objectives. The results show that Indonesia has successfully justified the alignment of its Negative Investment List policy regarding endangered fish species, listed in Appendix I of CITES juncto Article XX of the GATT 1994. On another note, the Dispute Settlement Body may issue rulings with differing considerations. Nonetheless, the WTO Agreement and CITES are provisions established to provide adequate negotiation space for all their members. Thus, CITES and WTO member states should refrain from raising disputes over Indonesia’s investment measures if it restricts their economic interests and market access within Indonesia. Therefore, it is recommended that the WTO and CITES members recognize and appreciate the Negative Investment List policy in maintaining a balance between investment development and the protection of endangered fish species. Furthermore, stakeholders are urged to delve deeper into the principles and objectives of the WTO and CITES Agreements. Additionally, the members of the relevant organizations must collaborate in a spirit of solidarity and environmental awareness, prioritizing dialogue, consultation, and negotiation over dispute legal action that could complicate the situation. In this context, multilateral dialogue can serve as an effective platform for mediating diverse interests and seeking sustainable solutions that benefit the economy and the conservation of endangered fish species.